Comparative and international education : an introduction to theory, method, and practice - Phillips, David, 1944 December 15-; Schweisfurth, Michele, 1962- (London : Bloomsbury Academic, 2014)
'Comprehensive introduction to comparative and international education'--
Includes bibliographical references and index.
Keywords: Comparative education; International education; Education -- Cross-cultural studies